Kiai's Leadership in Providing Inspiration and Motivation in Islamic Boarding Schools - Subchi, Muhammad; Dermawan, Oki; Ayu, Sovia Mas (Journal of Advanced Islamic Educational Management, 2024)
Pondok Pesantren, as a traditional Islamic educational institution, is not only a place to acquire religious knowledge, but also a center for character building and leadership. In the midst of the complexity of challenges faced by the younger generation of Muslims, the role of a kiai in providing inspiration and motivation is very important. As an authoritative and exemplary figure, the kiai is not only a spiritual leader, but also a source of inspiration capable of mobilizing santri to achieve their best potentialThis study is a descriptive qualitative research.  The purpose of this study is to analyze the leadership of kiai in providing motivation and inspiration at Darul Falah Islamic Boarding School in Bandar Lampung, Indonesia. Descriptive qualitative research, which is research that aims to describe in detail and in depth a social phenomenon by collecting data through observation, interviews, and document analysis. Based on the results of the study, it is concluded that the ability of Kiai in providing inspiration and motivation in Darul Falah Islamic Boarding School is carried out through, Kiai in Darul Falah Islamic Boarding School Bandar Lampung shows the ability to provide inspiration and motivation to students to realize the vision of the five souls of the cottage, a structured teaching system, a supportive parenting pattern, and an integrated curriculum are important factors that support this process, and the internalization of the values of Pancajiwa Pondok in daily life becomes the basis for forming a solid and virtuous character of students.